Time-dependent resilience as a generalization of time-dependent reliability - ICASP14; Wang, Cao; Ayyub, Bilal (My University, 2023)
Civil structures and infrastructures are often subjected by design to the impacts of natural and human-caused hazardous events, and accordingly may suffer from damages, functionality loss, and failure. In order to quantitatively measure the associated likelihood and consequences for quantifying risks, an appropriate measure of structural reliability and resilience is essentially required. This paper presents an explicit measure for the time-dependent resilience of repairable structures as a natural extension of time-dependent structural reliability concepts, taking into account the effects of structural performance deterioration and nonstationary external loads. The proposed resilience measure is a function of the duration of considered service period, and is in a closed form. Remarkably, the time-dependent resilience can be treated as a generalized form of the time-dependent reliability. A numerical example is presented to demonstrate the accuracy and applicability of the proposed resilience measure.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED